The Effects of Eczefolia™ on The Migration and Invasion of Colon Cancer Cells - Mara Ridhuan, Nur Sorfeena Sufi; Md Hashim, Nur Fariesha; Abdullah, Nurul Akmaryanti; Zakuan, Noraina Muhamad (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Colon cancer ranks third as the most common cancer globally with metastasis being the primary cause of mortality. The progression of metastasis is shown to significantly worsen the prognosis of cancer patients. Therapeutic interventions such as radiotherapy, chemotherapy and surgery utilised in treating colon cancer are receiving drawbacks due to manifestation of adverse side effects, drug resistance and disease recurrence. Therefore, increasing attention has been directed towards alternative therapeutic methods using natural products to lessen the drawbacks. Eczefolia™ is an enriched extract of Melicope Ptelefolia (MP), commonly known as ‘Tenggek Burung’ in Malaysia, which has recently shown to have anticancer effects. It is enriched with 2,4,6-Trihydroxy-3-geranyl acetophenone (tHGA) which is shown to exhibit anti- inflammatory, antioxidant, anti-allergic and anticancer properties. This study may provide preliminary insights on its anticancer properties of Eczefolia™, specifically on the inhibition of migration and invasion of colon cancer cells. Methods: HCT116 colon cancer cells were exposed to various concentrations of Eczefolia™ ranging from 3.9 μg/mL to 1000 μg/mL to determine its cytotoxic effect and inhibitory concentration (IC20 and IC50) using MTT assay. Subsequently, scratch migration assay and transwell invasion assay were performed to determine the migratory and invasive capabilities of colon cancer cells following Eczefolia™ treatment. Results: The IC20 and IC50 could not be obtained from the MTT assay, suggesting the IC50 > 1000 ug/ml. A significant reduction in the percentage of cell migration and invasion of HCT116 cells was observed in Eczefolia™ at a concentration of 1000 μg/mL (p < 0.05). Conclusion: Eczefolia™ does not exhibit cytotoxic properties towards HCT116 cells but shows anti- migratory and anti-invasion properties at a high concentration. Therefore, it may be a potential therapeutic candidate for treatment of colon cancer metastasis. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S11